2018
DOI: 10.4103/0973-1482.176175
|View full text |Cite
|
Sign up to set email alerts
|

Role of human Cytomegalovirus in the etiology of nasopharyngeal carcinoma

Abstract: The present study has shown a relatively considerable association between HCMV and NPC. The great majority of samples sheltering HCMV were also found to hide EBV, which proposes the potentiality of EBV over HCMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…The pro-tumor effect persists even after conducting multivariate analysis, implying that HCMV could be a potential oncogenic agent in said malignancies. Our results are related with those reported by Ahmed et al and Chan et al, both of who have detected HCMV in a significant proportion of patients with nasopharyngeal cancer [35,36]. However, it is worthwhile noting that a 1983 study found no association between HCMV infection and nasopharyngeal malignancy [37].…”
Section: Discussionsupporting
confidence: 91%
“…The pro-tumor effect persists even after conducting multivariate analysis, implying that HCMV could be a potential oncogenic agent in said malignancies. Our results are related with those reported by Ahmed et al and Chan et al, both of who have detected HCMV in a significant proportion of patients with nasopharyngeal cancer [35,36]. However, it is worthwhile noting that a 1983 study found no association between HCMV infection and nasopharyngeal malignancy [37].…”
Section: Discussionsupporting
confidence: 91%
“…This is most obvious for nasopharyngeal carcinoma and gallbladder cancer. The link with NPC has already described in literature [63], which further corroborates our findings from a global perspective. Interestingly enough, in specific cases (23.3%) of malignancies where CMV generally correlated with cancer-prevention, in some age groups its effect would be statistically recognized as oncogenic (Table 2).…”
Section: At What Time Could CMV Offer Its Greatest Protection?supporting
confidence: 92%
“…This is most obvious for nasopharyngeal carcinoma and gallbladder cancer. The link with NPC has already described in the literature [63], which further corroborates our findings from a global perspective. Interestingly enough, in specific cases (23.3%) of malignancies where CMV generally correlated with cancer prevention, in some age groups, its effect would be statistically recognized as oncogenic (Table 2).…”
Section: When Might CMV Provide the Highest Level Of Protection?supporting
confidence: 92%